Spatially specific vs. unspecific disruption of visual orientation perception using chronometric pre-stimulus TMS - de Graaf, Tom A.; Duecker, Felix; Fernholz, Martin H. P.; Sack, Alexander T. (Frontiers in Behavioral Neuroscience, 2015)
Transcranial magnetic stimulation (TMS) over occipital cortex can impair visual processing. Such ‘TMS masking’ has repeatedly been shown at several stimulus onset asynchronies (SOAs), with TMS pulses generally applied after the onset of a visual stimulus. Following increased interest in the neuronal state-dependency of visual processing, we recently explored the efficacy of TMS at ‘negative SOAs’, when no visual processing can yet occur. We could reveal pre-stimulus TMS disruption, with results moreover hinting at two separate mechanisms in occipital cortex biasing subsequent orientation perception. Here we extended this work, including a chronometric design to map the temporal dynamics of spatially specific and unspecific mechanisms of state-dependent visual processing, while moreover controlling for TMS-induced pupil covering. TMS pulses applied 60-40 ms prior to a visual stimulus decreased orientation processing independent of stimulus location, while a local suppressive effect was found for TMS applied 30-10 ms pre-stimulus. These results contribute to our understanding of spatiotemporal mechanisms in occipital cortex underlying the state-dependency of visual processing, providing a basis for future work to link pre-stimulus TMS suppression effects to other known visual biasing mechanisms.